Educação Infantil: o lugar da Pedagogia e da Educação Física em uma perspectiva Sócio-Histórico-Dialética Infant Eductation: The Place of Pedagogy and of Physical Education in a Social-Historical-Dialectic Perspective (Universidade Federal de Goiás, 2006)
O objetivo deste artigo é realizar um exercício reflexivo sobre as relações entre Pedagogia e Educação Física e suas contribuições para a educação da infância em uma perspectiva sócio-histórico-dialética. Para isso, organizamos os textos em três momentos: o primeiro tem como finalidade resgatar a constituição histórica dos projetos em educação infantil no Brasil; o segundo busca delimitar as proposições fundamentais da perspectiva sóciohistórico-dialética, e, por último, indicamos caminhos a serem percorridos pelas duas áreas de conhecimento em debate, Educação Física e Pedagogia. PALAVRAS-CHAVE: Educação infantil - Pedagogia - Educação The aim of this article is to reflect upon the relations between Pedagogy and Physical Education and their contributions to infant education in a social-historical-dialectic perspective. To achieve this, we have organized this text in three parts: the first one aims at recollecting the historical constitution of projects on infant education in Brazil; the second part aims at defining the scope for thefundamental propositions of this social-historicaldialectic perspective. Lastly, we indicate paths that can be followed by these two fields of knowledge that are discussed here, physical education and pedagogy. KEY WORDS: Infant education - Pedagogy - Physical education.